Intra-urban residential differentiation in the post-Soviet city: the case of Riga, Latvia - Krišjane, Zaiga; Berzinš, Maris (Hungarian Geographical Bulletin, 2014)
Cities in many Central and Eastern European (CEE) countries have transformed rapidly since the political and socio-economic restructuring started in the early 1990s. Economi reforms, growing income inequalities, changes in housing system and selective residential mobility are resulting in increasing socio-spatial differentiation among urban neighbourhoods also in Riga. In addition, litt le is known about the ethnic dimension of intra-urban residential differentiation, despite the existence of sizeable minority populations. The focus on ethnicity is important, since Riga is the only capital city in the Baltic States where the ethnic majority is outnumbered by the non-Latvian minority. This paper provides empirical evidence about socio-spatial differentiation in Riga according to its ecological structure. Our aim is to examine the characteristics of the inhabitants by distinctive types of urban neighbourhoods with particular interest on ethnicity. The analysis is based on a recent sample survey that was carried out in 2012 and 2013. The results reveal that characteristics of population subgroups differ among urban zones with regard to ethnic origin, age, household size and income. Less pronounced are differences by education, migration background and family type. The conclusion is that Riga is a relatively mixed city at the beginning of the 21st century.